What if Cyberspace Were for Fighting?. Issue 4 (7th December 2018) - Hollis, Duncan B.; Ohlin, Jens David
Abstract: This essay explores the ethical and legal implications of prioritizing the militarization of cyberspace as part of a roundtable on "Competing Visions for Cyberspace." Our essay uses an ideal type—a world that accepts warfighting as the prime directive for the construction and use of cyberspace—and examines the ethical and legal consequences that follow for (i) who will have authority to regulate cyberspace; (ii) what vehicles they will most likely use to do so; and (iii) what the rules of behavior for states and stakeholders will be. We envision a world where states would take on a greater role in governance but remain constrained by law, including jus ad bellum and jus in bello criteria, but also sovereignty, nonintervention, and self-determination. We ask if the net result would mean states causing less harm than they do in kinetic conflicts. Ultimately, our essay takes no position on whether cyberspace should be a militarized domain (let alone one where warfighting is the prime directive). Rather, our goal is to situate a warfighting cyber domain within the reality of a pluralist cyberspace, where ethical imperatives compete or coalesce to support specific governance mechanisms.